Revision of strategies for approaches to the management of water at global and Latin American level (REVISTA NODO, 2019)
Since the water resource is a fundamental element to guarantee the environmental, social and economic security of the present and future human development, it is important to prioritize the care and recovery of water sources since these are fundamental in the main ecological structure of the Cities around the world and that is why management strategies in the resolution of the water conflict are key.Therefore, this article aims to carry out a bibliographic review based on international references that allow the identification of management strategies by approaches that have been developed over the last twenty years (1998-2018) around water sources worldwide and giving a special focus to Latin America. This review aims to perceive where the solutions of the different problems that are woven around the water resource are being directed and thus identify which are the strategies that have yielded the best results.
Keywords: Water management; Conflicts; Strategies